Masa Depan Pendidikan Hukum Islam Di Perguruan Tinggi Keagamaan Islam Refleksi Pembelajaran Di Masa Kedaruratan COVID-19 - Fattah Setiawan Santoso (Universitas Cokroaminoto Yogyakarta, 2020)
This writing is a reflection of Islamic Law education at PTKI during the Emergency COVID-19. Through a literature review on Islamic law education and research, some basic material in Islamic law can be formulated that is useful in equipping students in responding to the internet as a source of learning. The proposed learning method then is a comparative method of law which has been ingrained in the dynamics of Islamic law since the early days of the growth of Islamic law